THE EFFECT OF VEHICLE VOLUME ON DAMAGE TO PINE ROAD IN PALANGKA RAYA CITY - Lola Cassiophea; ary, Ary Andreo Siregar (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
Along with the level of traffic density that crosses the Pinus road, there are several obstacles that cause damage, one of which is the damage that occurs in the road construction section, which is caused by the load of vehicles with excessive loads such as trucks, which further causes damage to the road, namely an increase in volume. heavy traffic every day. Asphalt pavement is generally used on roads that have a fairly dense traffic volume, with the increase in the number of vehicles resulting in damage in a relatively short time than planned. The purpose of this study is to determine the effect of the volume of vehicle types on road damage on asphalt pavement, it can be predicted earlier the value of road damage that will occur, the method used in this study is the method of analyzing vehicle volume on road damage with the regression method. Used to obtain the relationship function with the value of R² (coefficient of determination) which shows the magnitude of the effect of changes in the volume of vehicle types on changes in the value of road damage, this study was carried out on the Pinus road, Palangka Raya City. There is a relationship between the volume of vehicle types and the value of road damage, the results obtained are R² = 0.744 which shows that road damage is influenced by the volume of heavy vehicles, light vehicles and motorcycles with a percentage value of 74.4%. From the results of the equation between heavy vehicles (X1), light vehicles (X2), motorcycles (X3), and the value of road damage Y = 0.159 X1 + 0.034 X2 + 0.017 X3 + 14,189. From these equations it can be described as follows, the regression coefficient (X1) (a) = 0.159 means that a heavy vehicle of 100 vehicles/day will increase the level of road damage by 5.9, the regression coefficient (X2) (b) = 0.034 means a light vehicle of 100 vehicles/day will increase the level of road damage by 3.4, Regression coefficient (X3) (c) = 0.017 means that 100 motorbikes/day will increase the level of damage by 1.7, constant (c) = if there are no vehicles driving passing a road segment, the road will experience road damage of 14,189.